Repeated collaboration of inventors across European regions - Gergő Tóth; Zoltán Elekes; Sándor Juhász; Balázs Lengyel (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
This paper explores the spatial patterns and underlying determinants of repeated inventor collaboration across European NUTS 3 regions. It is found that only a small fraction of co-inventor linkages across regions are repeated, while community detection reveals that these collaborations are clustered in geographical space more intensively compared with collaboration in general. Additional results from gravity modelling indicate that links in the inter-regional co-patenting network emerge mainly through the triadic collaboration of regions, while geographical proximity becomes the most influential factor for repeating co-inventor ties. In addition to that, the combination of technological similarity and shared third partner regions offer a premium for the likelihood of repeating collaboration, but only when geographical proximity is present as an enabler.
Keywords: D85; O31; O43; O52; R11; R58; 330; collaborative knowledge production; inter-regional collaboration; co-inventor network; repeated collaboration; European Research Area; gravity model